Development of Augmented Reality-Assisted Practical Guide Media for Thermochemistry Practicum and Its Effectiveness in Improving Students' Learning Outcomes - Giska Amirah; Ira Mahartika; Suyanta (Postgraduate, University of Mataram, 2025)
The governments’s goal to produce graduates able to compete in all technology era must be realized by using media with technological assistance in the learning process. Chemistry learning focuses on providing direct experience which can be in the form of practical work activities. The limitations of laboratory facilities, tools, and practical work materials hinder the implementation of practical work activities, but this can be minimized, one of which is with Augmented Reality assistance. This research aimed at producing Augmented Reality assisted practicum guide media in Thermochemistry practice that was valid and practical based on the result of validity test by material, media and language experts and practical test by chemistry teacher and students. Research and Development method was used in this research with ADDIE research design, and the steps were (1) Analyze, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. Material experts validation result have a percentage 80% with valid category, media experts have a percentage 79,6% with valid category and linguist have a percentage 100% with very valid category. The percentage of practicality test by Chemistry subject teachers was 82% with very practical category, and the percentage of student response practicality test was 86% with very practical category. Based on the test result of validity and practicality it could be concluded that Augmented Reality assisted practicum guide media in thermochemistry practice was very appropriate and practical to be used as a learning on thermochemistry. This practicum guide has also been tested for its effectiveness on students' learning outcomes using a Single group pretest-posttest design. The results of the non-parametric test with the Mann-Whitney test obtained a calculated Uhitung of -132. This value is smaller than its Utabel of 123, which means that H0 is rejected and Ha is accepted. It can be concluded that there is a difference in students' learning outcomes in learning chemistry between classes that apply Augmented Reality-assisted practicum guide media or not in thermochemistry practicums.